Influence of mild cognitive impairment on clinical and functional prognosis in older candidates for cardiac surgery - Harmand, Magali González-Colaço; Mata, María; Prada-Arrondo, Pablo César; Domínguez-Rodríguez, Alberto; Barroso, José; Galtier, Ivan (Frontiers in Human Neuroscience, 2024)
In this study, we analyzed the prognostic impact of mild cognitive impairment (MCI) prior to cardiac surgery on 12-month clinical outcomes in older patients. Method: We performed a longitudinal prospective study of 48 patients undergoing cardiac surgery and 26 neurologically healthy participants aged 65 years or older. All participants underwent a neuropsychological assessment. Functional status, quality of life and frailty were assessed in candidates for surgery. One year after surgery, 24 patients remained in the study. Results: MCI was diagnosed in 35% of the patients at baseline. Postsurgical changes in functionality consisted of a tendency toward impaired basic activities of daily living (BADL) in the MCI group and a statistically significant worsening in instrumental activities of daily living (IADL) in women with MCI. Changes in quality of life consisted of a significant improvement in anxiety-depression in the MCI group and a tendency toward greater pain-discomfort in the non-MCI group. Cognitive status significantly declined only in the non-MCI group. Neither group showed significant changes in frailty. Relative risk analysis showed that patients with a diagnosis of MCI at baseline had a higher risk of cognitive decline at follow-up, while those without a diagnosis of MCI at baseline had a lower risk of impaired IADL. No association was found between MCI and resource use. Preoperative impairment in memory, visuospatial and executive functions was significantly associated with loss of quality of life at followup. Impairment of memory and visuospatial function was significantly associated with cognitive decline. Preserved memory was associated with a lower risk of impaired BADL at follow-up.The present study provides clue on the impact of MCI in candidates for cardiac surgery. Preoperative detection of cognitive impairment could be highly valuable to help guide preand post-operative management.